Gendering Macroeconomic Analysis and Development Policy: A Theoretical Model. Issue 3 (3rd July 2022) - Onaran, Özlem; Oyvat, Cem; Fotopoulou, Eurydice
Abstract : The aim of this study is to develop a feminist Post-Keynesian/Post-Kaleckian model to theoretically analyze the effects of labor market and fiscal policies on growth and employment. The study develops a three-sector gendered macroeconomic model with physical and social sectors (health, social care, education, childcare) in the public and private market economy, and an unpaid reproductive sector providing domestic care. It provides a theoretical analysis of the effects on GDP, productivity, and employment of men and women in both the short and long run, as a consequence of (1) fiscal policies, in particular public spending on social infrastructure, and (2) decreasing gender wage gaps, particularly within the social sector dominated by women. This theoretical analysis provides a basis to further analyze the impacts of an upward convergence in wages, other types of fiscal spending, and taxes. HIGHLIGHTS The study develops a feminist Post-Keynesian model to aid policy analysis and gender-responsive budgeting. Public social expenditure decreases gender inequality by reducing women's unpaid work burden. Social spending creates more employment for women than physical infrastructure and closes gender gaps in employment. Social spending can increase productivity, partially moderating the employment impact of spending. If the economy is wage-led, more progressive taxes increase output.